Sedimentation, metamorphism and granite generation in a Back-Arc Region : the crustal processes recorded in the Ediacaran Nova Venécia Complex (Araçuaí Orogen, Southeast Brazil). - Richter, Fabiana (2015)
Programa de Pós-Graduação em Evolução Crustal e Recursos Naturais. Departamento de Geologia. Escola de Minas, Universidade Federal de Ouro Preto.